Indicators and countermeasures of modern slavery in global supply chains: Pathway to a social supply chain management framework - Frank Bodendorf; Fabian Wonn; Kristin Simon; Jörg Franke (Business Strategy and the Environment, 2022)
Even though global supply chains are (usually unintentionally) tied to slave labor, research and practice have largely ignored the issue. This is expected to change as civil society activism and new legislation increase the risk of litigation and reputational damage to supply chain partners. To deal with and combat modern slavery in the supply chain, a theory inspired social supply chain management framework consisting of indicators and countermeasures of modern slavery in the supply chain is developed. The framework is refined in a qualitative expert interview study. The theoretical framework is then evaluated by a multimethod empirical analysis that includes a multicase study based on publicly available supply chain data from 6000 media articles and company websites as well as a quantitative empirical study based on survey data from 280 corporate sustainability experts operating in global supply networks. The results show that economic, political-legal, social, and environmental factors have a significant impact on contemporary slavery in the supply chain. The study also motivates supply chain partners to use preventative and detective measures to reduce the probability of encountering modern slavery actions in their supply chain. Theoretical and managerial implications are drawn from the findings, pointing to a holistic approach to combatting modern slavery in the supply chain.
Keywords: 330; modern slavery; multi-method; sustainable supply chain management